2004
DOI: 10.1081/ada-120037375
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Drug Users' HIV‐Risk Behaviors with Primary/Other Partners

Abstract: The objective of this study was to determine how injection drug users' (IDUs) HIV-risk behavior differs with primary and other sex partners. Interviews were conducted with injection drug users from a needle exchange program (n = 243). Those with one sexual partner were more likely to report never using condoms with primary partners than were those with more than one partner (74% vs. 54%, p < 0.001). Those with more than one partner differed, between primary and other sexual partners, in their disclosure of HIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 20 publications
5
23
0
1
Order By: Relevance
“…Consistent condom use by male IDUs is reportedly low and condom use is often less common with their primary sexual partners than with casual sexual partners [35], thus women with IDU sex partners are at risk from their partners' risk behaviors with both sexual and injecting partners. In our study, women with severe immunosuppression were substantially more likely to be diagnosed with a STI, independent of other factors.…”
Section: Discussionmentioning
confidence: 96%
“…Consistent condom use by male IDUs is reportedly low and condom use is often less common with their primary sexual partners than with casual sexual partners [35], thus women with IDU sex partners are at risk from their partners' risk behaviors with both sexual and injecting partners. In our study, women with severe immunosuppression were substantially more likely to be diagnosed with a STI, independent of other factors.…”
Section: Discussionmentioning
confidence: 96%
“…At the end of 2004, 26% of cumulative AIDS cases were attributed solely to injection drug use (CDC, 2005) while this estimate climbs to over one-third (36%) of cases since the beginning of the epidemic when considering indirect transmission (e.g., sexual contact with an injection drug user). Indeed, recent studies have shown the potential of injection drug users (IDUs) to not only acquire HIV through injection drug use, but also to transmit HIV to the larger population through their engagement in sexual risk behavior (Houlding & Davidson, 2003;Kuyper et al, 2004;Rosengard, Anderson, & Stein, 2004;van Empelen, Schaalma, Kok, & Jansen, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Research indicates that drugs affect a person's ability to make good judgments and increase engagement in impulsive, often dangerous behaviors (Wistanley, Gust, and Strathdee, 2006) such as having multiple sexual partners and increased length of sexual encounters (Rosengard, Anderson, and Stein, 2004;Semple, Patterson, and Grant, 2004). Numerous international and African studies have shown that condom use among the drug-using population is at best inconsistent (Abdool et al, 2006;Dewing et al, 2006;McCurdy, Williams, Kilonzo, Ross, and Leshabari, 2005), very infrequent with oral sex (Semple et al, 2004), and more likely to be used with casual partners than regular partners (Des Jarlais and Salaam, 2005;McCurdy et al, 2005;Rosengard et al, 2004).…”
Section: Introductionmentioning
confidence: 99%